Right heart catheterization using antecubital venous access: Feasibility, safety and adoption rate in a tertiary center. Issue 1 (9th November 2013) - Shah, Sachin; Boyd, Graham; Pyne, Christopher T.; Bilazarian, Seth D.; Piemonte, Thomas C.; Jeon, Cathy; Waxman, Sergio
<x xml:space="preserve">Abstract</x> Objectives To determine feasibility, safety, and adoption rates of right heart catheterization (RHC) using antecubital venous access (AVA) as compared to using the traditional approach of proximal venous access (PVA). Background RHC via PVA (i.e., internal jugular, femoral or subclavian) is generally a low risk procedure; however, complications may occur and are usually access site related. RHC via an antecubital approach has regained attention given the increase in transradial left heart catheterizations. Methods Patients undergoing RHC for any indication at a single large academic medical center were identified over a 5‐year period (January 2008 to December 2012) from a database. Medical records were retrospectively analyzed for demographic, procedural and outcomes data. Results Two hundred seventy‐two RHC procedures were included (106 AVA, 166 PVA). The adoption rate of AVA for RHC increased rapidly since its introduction in our laboratory in 2010 (100% PVA in 2008 and 2009, 85% AVA in 2012). All procedures were successful; however, 6% of procedures required additional, alternate access to the original site. Initial success rates were similar in the two groups (91 vs. 96% for AVA and PVA respectively, P = 0.12). Fluoroscopy time was shorter in the group of patients who underwent the procedure via AVA. The complication rate was 0% in the AVA group compared with 3% in the PVA group (P = 0.16). Conclusion RHC via the AVA is a feasible and safe alternative to PVA. Our experience and rapid adoption support the use AVA as the access site of choice for RHC in uncomplicated patients. © 2013 Wiley Periodicals, Inc.